Biodegradation of unctuous wastes of food industry - Kis Ágnes; Laczi Krisztián; Tengölics Roland; Kovács K. L.; Rákhely Gábor; Perei K.; International Symposium on Analytical and Environmental Problems (17.) (2011) (Szeged) Szeged 2011. szeptember 19. (SZAB Szeged, 2012)
Nowadays, industrial emission of harmful materials is an extremely acute problem for humanity and Nature. Technologies with low or zero emission is of key importance to minimize the contamination of the ecosystem. However, vast amount of hazardous substances still gets out into the environment which must be made harmless. Bioremediation technologies using microorganisms to neutralize polluting materials are environmentally sound and economical tools for removal toxic compounds. It is a well-known fact that several Rhodococcus sp. can degrade a wide range of hazardous chemicals, such as aliphatic and aromatic hydrocarbons. In our laboratory, a Rhodococcus sp. was isolated from hydrocarbon polluted sites and it was successfully proven that the bacterium could efficiently degrade industrial hydrocarbons such as diesel oil and dead oil. The strain could tolerate low temperature and certain salt concentrations therefore it might be applied in oil mineralization after marine catastrophes. In this study, our aim was to test the ability of this strain to degrade food industrial and municipal waste. Lard, pig and poultry fat and cooking oil were used as sole carbon sources in minimal medium. The substrate utilization was demonstrated indirectly by measuring the respiration activity and CO2 production of the Rhodococcus sp. The strain could grow even at 10 g/1 of hydrocarbon concentration, it consumed the available oxygen and released remarkable amount of carbon dioxide within a week. These facts make this strain a promising waste cleaner both in food industrial applications and housekeeping.
Keywords: Műszaki és technológiai tudományok; Környezeti biotechnológia